Quantum Computing In The Cloud – A Systematic Literature Review - Amirul Asyraf Zhahir; Siti Munirah Mohd; Mohd Ilias M Shuhud; Bahari Idrus; Hishamuddin Zainuddin; Nurhidaya Mohamad Jan; Mohamed Ridza Wahiddin (Josip Juraj Strossmayer University of Osijek, 2024)
Indexed by WOS